2018
DOI: 10.1002/jlb.1ru0818-310r
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage immunomodulation in chronic osteolytic diseases—the case of periodontitis

Abstract: Periodontitis (PD) is a chronic osteolytic disease that shares pathogenic inflammatory features with other conditions associated with nonresolving inflammation. A hallmark of PD is inflammation‐mediated alveolar bone loss. Myeloid cells, in particular polymorphonuclear neutrophils (PMN) and macrophages (Mac), are essential players in PD by control of gingival biofilm pathogenicity, activation of adaptive immunity, as well as nonresolving inflammation and collateral tissue damage. Despite mounting evidence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 190 publications
(410 reference statements)
2
84
0
Order By: Relevance
“…Our laboratory and others have shown that LPS increases ASMase‐mediated SM hydrolysis and CER production by stimulating ASMase activity, leading to an increase in inflammatory response of macrophages (Jin et al, ; Sakata et al, ). Given the importance of macrophages in periodontitis (Sima, Viniegra, & Glogauer, ), these findings suggest that ASMase may mediate LPS‐induced periodontitis, and it is thus expected that ASMase deficiency would reduce LPS‐triggered periodontitis. However, the result of this study is unexpected as it showed that ASMase deficiency exacerbated LPS‐induced periodontitis in animal model.…”
Section: Discussionmentioning
confidence: 79%
“…Our laboratory and others have shown that LPS increases ASMase‐mediated SM hydrolysis and CER production by stimulating ASMase activity, leading to an increase in inflammatory response of macrophages (Jin et al, ; Sakata et al, ). Given the importance of macrophages in periodontitis (Sima, Viniegra, & Glogauer, ), these findings suggest that ASMase may mediate LPS‐induced periodontitis, and it is thus expected that ASMase deficiency would reduce LPS‐triggered periodontitis. However, the result of this study is unexpected as it showed that ASMase deficiency exacerbated LPS‐induced periodontitis in animal model.…”
Section: Discussionmentioning
confidence: 79%
“…The monocyte-macrophage plays an important role both in the adaptive immune response and innate immunity [6]. Plenty of evidences show that macrophages derived from circulating mononuclear cells and tissue resident cells exist in the diseased tissues of periodontitis and are leading players in immunoreaction against periodontal pathogens, contributing to the initiation of periodontal inflammation [7,8]. The number of macrophages and macrophagessecreted pro-inflammatory cytokines including IL-1, IL-8, TNF-α and so on are elevated in periodontitis-associated gingival tissue biopsies [9].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas CXCL1 is a strong chemoattractant for neutrophils, CCL2 and CCL5 mainly promote the recruitment of monocytes, macrophages, and lymphocytes [13]. Several studies have clearly demonstrated that these cell types and their subsets have defined roles in the battle between the host and microorganisms in periodontitis [21,22].…”
Section: Discussionmentioning
confidence: 99%